Dissociative Disturbance in Hangul-Hanja Reading after a Left Posterior Occipital Lesion - Key-Chung Park; Sung-Sang Yoon (Behavioural Neurology)
Since the Korean language has two distinct writing systems, phonogram (Hangul) and ideogram (Hanja: Chinese characters), alexia can present with dissociative disturbances in reading between the two systems. A 74-year-old right-handed man presented with a prominent reading impairment in Hangul with agraphia of both Hangul and Hanja after a left posterior occipital- parietal lesion. He could not recognize single syllable words and nonwords in Hangul, and visual errors were predominant in both Hanja reading and the Korean Boston Naming Test. In addition, he had difficulties in visuoperceptual tests including Judgment of Line Orientation, Hierarchical Navon figures, and complex picture scanning. These findings are consistent with the hypothesis that Hangul reading impairment results from a general visual perceptual deficit. However, this assumption cannot explain why performance on visually complex Hanja was better than performance on visually simple Hanja in our patient. In addition, the patient did not demonstrate higher accuracy on Hanja characters with fewer strokes than on words with more strokes. Thus, we speculate that the left posterior occipital area may be specialized for Hangul letter identification in this patient. This case demonstrates that Hangul-Hanja reading dissociation impairment can occur after occipital-parietal lesions.